Impairment of Oligodendroglia Maturation Leads to Aberrantly Increased Cortical Glutamate and Anxiety-Like Behaviors in Juvenile Mice - Chen, Xianjun; Zhang, Weiguo; Li, Tao; Guo, Yu; Tian, Yanping; Wang, Fei; Liu, Shubao; Shen, Hai-Ying; Feng, Yue; Xiao, Lan (Frontiers in Cellular Neuroscience, 2015)
Adolescence is the critical time for developing proper oligodendrocyte (OL)-neuron interaction and the peak of onset for many cognitive diseases, among which anxiety disorders display the highest prevalence. However, whether impairment of de novo OL development causes neuronal abnormalities and contributes to the early onset of anxiety phenotype in childhood still remains unexplored. In this study, we tested the hypothesis that defects in OL maturation manifests cortical neuron function and leads to anxiety-like behaviors in juvenile mice. We report here that conditional knockout of the Olig2 gene (Olig2 cKO) specifically in differentiating OLs in the mouse brain preferentially impaired OL maturation in the gray matter of cerebral cortex. Interestingly, localized proton magnetic resonance spectroscopy revealed that Olig2 cKO mice displayed abnormally elevated cortical glutamate levels. In addition, transmission electron microscopy demonstrated increased vesicle density in excitatory glutamatergic synapses in the cortex of the Olig2 cKO mice. Moreover, juvenile Olig2 cKO mice exhibited anxiety-like behaviors and impairment in behavioral inhibition. Taken together, our results suggest that impaired OL development affects glutamatergic neuron function in the cortex and causes anxiety-related behaviors in juvenile mice. These discoveries raise an intriguing possibility that OL defects may be a contributing mechanism for the onset of anxiety in childhood.